The `Adventurers of England' on Hudson bay : a chronicle of the fur trade in the North - Laut, Agnes C. (Agnes Christina), 1871-1936. (Toronto : Glasgow, Brook, 1920)
Includes index. Bibliography p. 125-128. Mode of access: Internet.